A comparative survey of the status and application of Islamic Law in the legal system of Malaysia and Nigeria - Mokhtar, Khairil Azmin; Oba, Abdulmumini A (2011)
The experiences of Malaysia and Northern Nigeria of British colonialism and its impact of Islamic law are parallel in many respects. Before the advent of British colonization, Islamic Law was the Lex loci (Law of the Land) of the Malay States (that later became Malaysia) and that of the Sokoto and Kanem-Bornu Caliphates in what became Northern Nigeria. The Shariah Courts and local laws based on Shariah had been in existence in the Malaccan Sultanate and the northern Nigeria since in the fifteenth century respectively. In both the Malay states and northern Nigeria, attempts were made to modify local customs to conform to Islam and to adopt Islamic law; the process can be seen in the various versions of the Malacca [code] and in the Islamic reform movements (jihad) in northern Nigeria.